CD14 gene polymorphisms associated with increased risk of bovine tuberculosis in Chinese Holstein cows. (February 2018) - Xue, Y.; Gao, W.N.; Chen, F.; Ma, B.B.; Zhou, F.; Hu, Z.G.; Long, T.; Zhao, Z.Q.
Highlights: Five common single nucleotide polymorphisms (SNPs) were identified in the CD14 gene of Chinese Holstein cattle. SNPs −5C/T and 613G/A were associated with bovine tuberculosis (BTB) susceptibility in Chinese Holstein cows. These two SNPs might be used as candidate genetic markers in breeding cows with natural resistance to BTB. Abstract: Cluster differentiation antigen 14 (CD14) is an important pattern recognition receptor protein in innate immunity. The aim of this study was to identify and assess the association of single-nucleotide polymorphisms (SNPs) in the CD14 gene with susceptibility to bovine tuberculosis (BTB) in Chinese Holstein cows. DNA samples from 517 Chinese Holstein cows (257 tuberculosis positive cases and 259 healthy controls) were collected from dairy farms in China. SNPs in the entire CD14 gene, including exonic regions, intronic regions and close to the 5′- and 3′-terminal untranslated regions, were detected by PCR, followed by direct sequencing. Five SNPs (−5C/T, 613G/A, 1023G/A, 1306G/A and 1326G/T) were found in the CD14 gene region. Significantly increased BTB susceptibility was evident in T allele carriers of −5C/T ( P < 0.001; odds ratio, OR 2.02; 95% confidence interval, CI 1.57–2.77), G allele carriers of 613G/A ( P < 0.001; OR 2.17, 95% CI 1.50–3.08) and TG haplotype carriers of both SNPs ( P < 0.001; OR 3.14, 95% CI 1.24–4.50). These results suggest that −5C/T and 613G/A are risk factors for BTB in Chinese Holstein cattle and might be used as candidate genetic markers in breeding cows with natural resistance to BTB.